Band offsets in new BN/BX (X = P, As, Sb) lateral heterostructures based on bond-orbital theory. Issue 34 (15th August 2018) - Zhou, Wenhan; Liu, Xuhai; Hu, Xuemin; Zhang, Shengli; Zhi, Chunyi; Cai, Bo; Guo, Shiying; Song, Xiufeng; Li, Zhi; Zeng, Haibo
Abstract : Identifying heterostructures with tunable band alignments remains a difficult challenge. Abstract : Identifying heterostructures with tunable band alignments remains a difficult challenge. Here, based on bond-orbital theory, we propose a series of new BN/BX (X = P, As, Sb) lateral heterostructures (LHS). Our first principles calculations reveal that the LHS interlines have a substantial impact on the electronic properties. Importantly, we start with the chemical concepts, such as bond length and strength as well as orbital overlap interaction, in an attempt to thoroughly investigate the electronic properties, namely the band offset, the band gap ( E g ) and the state of the energy level. We demonstrate that the newly designed BN/BX LHS have profound implications for developing advanced optoelectronics, such as high-performance light-emitting diodes and lasers. Furthermore, the new BN/BX LHS designed from the chemical viewpoint can shed new light on overcoming the enormous hurdle of ineffective and laborious material design.